Engaging in High-Intensity Interval Training is More Effective than Moderate-Intensity Interval Training in Improving Aerobic Capacity and Body Composition in Students - Arif Bulqini; Andri Suyoko; Machfud Irsyada; Imam Syafii; Nurkholis; David Agus Prianto; Muhammad; Achmad Rizanul Wahyudi; Laily Mita Andriana; Billy Emir Rizkanto; Adi Pranoto (Physical Education Theory and Methodology)
Objectives. This study aimed to prove the difference in the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on increasing aerobic capacity and improving body composition.